South African Exporters and the Global Crisis: Intensive Margin Shock, Extensive Margin Hangover. (26th May 2015) - Matthee, Marianne; Farole, Thomas; Naughtin, Tasha; Rankin, Neil
Abstract: This paper examines how changes at the intensive (established exporters exporting existing products to established markets) and the extensive (new exporters, products or markets) margins contribute to South African export growth and how this was affected by the global financial crisis. We find that the intensive margin is the more important contributor to export growth, contributing more than three quarters of observed growth. The intensive margin contracted significantly during the global financial crisis of 2009 but bounced back to pre‐crisis levels quickly. However, the impacts on the extensive margin persisted after the crisis with lower levels of entry of firms, new products and new destinations. The short‐term impact of the crisis was mitigated by the concentration of South African exports among larger, more productive super‐exporters. However, the fall in entry of new firms, products and destinations as a result of the crisis may mean that this concentration persists, and, at least over the next few years, South Africa does not diversify and broaden its exports.